Supply Chain Quality Management 4.0 for Sustainable Performance Excellence in FMCG Companies - Le Trong Bang, Quang (Digital Repository of Theses, 2026)
The rapid advancement of digital transformation, coupled with escalating sustainability pressures, has compelled the Fast-Moving Consumer Goods (FMCG) industry to fundamentally reconfigure its operational and quality management paradigms. While Industry 4.0 technologies promise enhanced transparency, integration, and efficiency, empirical evidence remains limited regarding how digitalization can be effectively integrated with supply chain quality management to drive sustainable performance, particularly in emerging market contexts. Addressing this research gap, the present study develops and empirically validates a comprehensive Supply Chain Quality Management 4.0 (SCQM4.0) framework and examines its impact on sustainable supply chain performance within the FMCG sector in Vietnam. Grounded in the Resource-Based View, Systems Theory, and the Technology–Organization–Environment framework, SCQM4.0 is conceptualized as a multidimensional integrative capability encompassing internal quality management practices, external supply chain integration, quality information systems, and sustainability-oriented quality management strategies, all reinforced by Industry 4.0 technology adoption. This conceptualization reflects the premise that sustainable performance is achieved not through isolated quality initiatives but through coordinated alignment of organizational processes, inter-firm collaboration, and digital enablement across the supply chain. A quantitative research design was employed, utilizing survey data from 250 managers and professionals across systematically selected FMCG enterprises. The proposed model was assessed using Structural Equation Modeling (SEM), including rigorous measurement validation and structural analysis to test the hypothesized relationships. The empirical findings demonstrate that SCQM4.0 practices exert a significant and positive influence on sustainable development performance across economic, environmental, and social dimensions, underscoring the strategic importance of quality-driven supply chain coordination. Among the core dimensions, supply chain integration emerges as the most influential driver, highlighting the critical role of collaborative alignment and information sharing among supply chain partners in achieving sustainability objectives. Moreover, the results reveal a nuanced moderating role of Industry 4.0 Technology Adoption (ITA). Although digital technologies theoretically function as enabling mechanisms that enhance coordination, traceability, and real-time quality control, the observed negative moderating effect indicates that current technological implementation in the Vietnamese FMCG context primarily acts as a compensatory mechanism for managerial and integration deficiencies rather than as a fully synergistic catalyst. This outcome is partly attributable to the uneven maturity of digital transformation, where advanced technologies such as Blockchain and IoT remain underutilized relative to established digital platforms. By offering a validated multidimensional measurement framework for SCQM4.0 and clarifying the contingent and context-dependent role of Industry 4.0 technologies in shaping sustainability outcomes, this study contributes to both theoretical advancement and managerial practice. The findings refine the conceptual understanding of digitally enabled quality management capabilities in emerging economies and provide actionable insights for FMCG firms seeking to strategically align quality management initiatives with digital transformation efforts to achieve resilient, transparent, and long-term sustainable supply chain performance. Keywords: SCQM 4.0, Industry 4.0, Sustainability, FMCG, Vietnam, Supply Chain Integration.